Effect of Creep Feeding on Productive and Reproductive Performance of BLRI Improved Non-Descript Deshi Chicken Under Semi-scavenging Rearing System (Journal of the Bangladesh Agricultural University, 2024)
The study was conducted to evaluate the effects of creep feeding on productive and reproductive performance of BLRI improved Non-descript Deshi (ND) chicken and their chick’s growth up to 8th week of age under semi-scavenging conditions at three different locations of Bangladesh. Two groups of farmers were selected from each location having the BLRI improved ND birds where one group used creep feeder and followed improved management practices, called creep feeding (CF) group. Another group of farmers rear ND chicken traditionally without using creep feeder, termed as non-creep feeding group (NCF) or control group. In CF trial, feeding groups had significant effects on hen weight loss during incubation, resume of laying, clutch size and clutch length (p0.05) between the groups but higher in CF group than the NCF group as 82 and 76%, and 76 and 70%, respectively. Notably, the 8th week chick weight was 200g more in CF group than NCF group and the mortality was significantly (p